Pemecahan Masalah Program Linier Mahasiswa Pendidikan Matematika dengan Kemampuan Number Sense Tinggi - Arjudin, Arjudin; Kurniati, Nani; Turmuzi, Muhammad; Wulandari, Nourma Pramestie (FKIP Universitas Mataram, 2024)
Problem solving in mathematics is a basic and fundamental ability that a person must master. However, previous research shows that students' problem solving abilities still tend to be in the medium and low categories. Many factors can cause students' low problem solving abilities, including number sense ability. The aim of this research is to describe linear programming problem solving for mathematics education students with high number sense abilities. This research is a descriptive qualitative research involving 36 third year Mathematics Education Study Program students who have taken linear programming courses. The instruments used were number sense ability test questions, problem solving test questions, and interview guidelines. The results of this research obtained information that there were 6 students with high number sense abilities, all of whom only reached the medium category in problem solving. In general, students in this category do not write complete information regarding the constraints of linear programming problems at the information gathering stage. In addition, students also do not carry out the re-checking stage of solving the problem because they feel confident with the answer given. However, this solution is not correct